Confiança nos relacionamentos interorganizacionais: mais do que uma simples questão de estratégia comercial - Roberta de Cássia Macedo (2014)
The aim of this study was to verify whether the companies that rely on their customers and suppliers (vertical relationships) also rely on their competitors (horizontal relationships). Thus, the main concern was to understand whether firms rely on customers, suppliers and competitors as a matter of strategic or a natural practice of collaborative company culture. The theoretical framework that anchored this study was the relational view, the theory of networks and social capital, passing by the concepts of logistics, supply chain, and the construct of trust as a basic framework for understanding the relationships. The methodological procedures, the empirical field study were the APLs furniture located in Arapongas, Mirassol, Ubá and Bento Gonçalves. The data were collected from questionnaires. The statistical technique used was multiple regression analysis. The trust construct was analyzed in the dimensions of benevolence and commitment. The results showed that companies that rely on their customers in benevolence dimension also trust their competitors. Therefore, we can say that confidently as integrative element of collaborative culture is present in both vertical and horizontal relationships when there is trust in customers.